2016
DOI: 10.1097/mlr.0000000000000486
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Population Benefits and Costs of Rituximab Therapy in the United States from 1998 to 2013 Using Real-World Data

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 29 publications
1
17
0
1
Order By: Relevance
“…In fact, hospitalization in Italy costs around € 800/day (excluding therapeutic interventions) [75]. These considerations closely match those with other experiences in immunology [75,76] and hematology [77].…”
Section: Rituximab (Rtx)supporting
confidence: 75%
“…In fact, hospitalization in Italy costs around € 800/day (excluding therapeutic interventions) [75]. These considerations closely match those with other experiences in immunology [75,76] and hematology [77].…”
Section: Rituximab (Rtx)supporting
confidence: 75%
“…Real‐world data are also used in health economic analyses. Cancer registry incidence data and outcomes data linked to Medicare claims were used to show rituximab's cost‐effectiveness for chronic lymphocytic leukemia and certain lymphomas in the United States …”
Section: Optimizing Cancer Medicine Researchmentioning
confidence: 99%
“…Three studies and two abstracts in FL met the eligibility criteria for final inclusion. One study assessed patients who received prior treatment [30], while the other four included only treatment-naïve patients [26,[31][32][33]. Treatment regimens, when reported, all incorporated the use of R in monotherapy or combination.…”
Section: Costs/resource Usementioning
confidence: 99%
“…The time horizon ranged from 1 year [30] to a lifetime [32,33]. Studies were conducted from the health care payer perspective, when reported [30][31][32]34]. Table 4 provides direct cost results, with direct drug and non-drug costs further depicted in electronic supplementary Table 5.…”
Section: Costs/resource Usementioning
confidence: 99%